Phα1β Spider Toxin Reverses Glial Structural Plasticity Upon Peripheral Inflammation - Tenza-Ferrer, Helia; Magno, Luiz Alexandre Viana; Romano-Silva, Marco Aurélio; da Silva, Juliana Figueira; Gomez, Marcus Vinicius (Frontiers in Cellular Neuroscience, 2019)
The incoming signals from injured sensory neurons upon peripheral inflammation are processed in the dorsal horn of spinal cord, where glial cells accumulate and play a critical role in initiating allodynia (increased pain in response to light-touch). However, how painful stimuli in the periphery engage glial reactivity in the spinal cord remains unclear. Here, we found that a hind paw inflammation induced by CFA produce robust morphological changes in spinal astrocytes and microglia compatible with the reactive phenotype. Strikingly, we discovered that a single intrathecal injection with venom peptides that inhibit calcium channels reversed all the glial pathological features of the peripheral inflammation. These effects were more apparent in rats treated with the Phα1β spider toxin (non-specific calcium channel antagonist) than ω-MVIIA cone snail toxin (selective N-type calcium channel antagonist). These data reveal for the first time a venom peptide acting on glial structural remodeling in vivo. We, therefore, suggest that calcium-dependent plasticity is an essential trigger for glial cells to initiate reactivity, which may represent a new target for the antinociceptive effects of Phα1β and ω-MVIIA toxins in inflammatory pain conditions